The Effect of A Practical Life-Based Digital Literacy Approach on Students’ Digital Competence and Workload Efficiency - Uswatun Hasanah; Arpinda Syifa'a Awalin (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2026)
This study examines the effect of a Practical Life-Based Digital Literacy (PLDL) approach on university students’ digital competence and workload efficiency within Islamic higher education. Guided by experiential learning theory and the DigComp 2.1 framework, the research investigates how practical life–oriented digital literacy activities contribute to students’ technological proficiency and task management. Data were obtained from 172 teacher education students who completed validated self-assessment instruments measuring digital competence and workload efficiency. ANOVA and MANOVA results indicate that the PLDL approach has a significant effect on digital competence (F = 12.636, p < 0.001) and workload efficiency (F = 7.000, p < 0.001), with the multivariate test (Wilks’ Λ = 0.220, p < 0.001) explaining 71.2% and 57.8% of variance in the respective outcomes. Students engaged in PLDL activities demonstrated stronger skills in digital information management, collaboration, and ethical and reflective technology use. These findings highlight PLDL as an effective experiential model for enhancing competence and efficiency, offering strategic insights for the digital transformation of Islamic higher education.